2013
DOI: 10.3390/md11093335
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Studies of Tentacle Extract from the Jellyfish Cyanea capillata in Isolated Rat Aorta

Abstract: Our previous studies demonstrated that tentacle extract (TE) from the jellyfish, Cyanea capillata, could cause a dose-dependent increase of systolic blood pressure, which seemed to be the result of direct constriction of vascular smooth muscle (VSM). The aim of this study is to investigate whether TE could induce vasoconstriction in vitro and to explore its potential mechanism. Using isolated aorta rings, a direct contractile response of TE was verified, which showed that TE could induce concentration-dependen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 40 publications
0
11
0
2
Order By: Relevance
“…A number of publications during 2012–2013 reported extracts or structurally uncharacterized marine compounds, with novel and interesting preclinical and/or clinical pharmacology: in vitro antimalarial activity in crude extracts from Fiji marine organisms using a semi-automated RNA fluorescence-based high-content live cell-imaging assay [10]; the first report of in vitro liver stage antiplasmodial activity and dual stage inhibitory potential of British seaweeds [11]; anti-hepatitis C virus activity affecting the viral helicase NS3 and replication, in crude extracts from the marine feather star Alloeocomatella polycladia [12]; anti-herpes simplex virus HSV-1 and HSV-2 activity in a purified sulfoglycolipid fraction from the Brazilian marine alga Osmundaria obtusiloba [13]; in vivo anti-inflammatory activity of a heterofucan from the Brazilian seaweed Dictyota menstrualis that inhibited leukocyte migration to sites of tissue injury by binding to the cell membrane [14]; in vivo antinociceptive and anti-inflammatory activity in a crude methanolic extract of the red alga Bryothamnion triquetrum [15]; in vivo anti-inflammatory activity in a sulfate polysaccharide fraction from the red alga Gracilaria caudata resulting in significant inhibition of neutrophil migration and cytokine release [16]; in vitro anti-inflammatory effect of a hexane-soluble fraction of the brown alga Laminaria japonica that inhibited nitric oxide, prostaglandin E 2 , interleukin (IL)-1β and IL-6 release from lipopolysaccharide-stimulated macrophages via inactivation of nuclear factor-κB transcription factor [17]; in vivo anti-inflammatory of a polysaccharide-rich fraction from the marine red alga Lithothamnion muelleri that reduced organ injury and lethality, as well as pro-inflammatory cytokines and chemokines, associated with graft-versus-host disease in mice [18]; in vivo clinical effectiveness in an osteoarthritis trial by PCSO-524 TM , a nonpolar lipid extract from the New Zealand marine green lipped mussel Perna canaliculus , which may offer “potential alternative complementary therapy with no side effects for osteoarthritis patients” [19]; enhanced antioxidant activity of chitosan nanoparticles as compared to chitosan on hydrogen peroxide-induced stress injury in mouse macrophages in vitro [20]; induction of concentration-dependent vasoconstrictive activity on isolated rat aorta by a tentacle extract from the jellyfish Cyanea capillata [21]; significant antioxidant effect of a sulfated-polysaccharide fraction of the marine red alga Gracilaria birdiae which prevented naproxen-induced gastrointestinal damage in rats by reversing glutathione depletion [22]; in vitro antioxidant properties of a polysaccharide from the brown seaweed Sargassum graminifolium (Turn.) that was also observed to inhibit calcium oxalate crystallization, a constituent of urinary kidney stones [23]; antioxidant activity in organic extracts from 30 species of Hawaiian marine algae, with the carotenoid fucoxanthin identified as the major bioactive antioxidant compound in the brown alga T. ornata [24]; screening of antioxidant activity in 18 cyanobacteria and 23 microalgae cell extracts identified Scenedesmus obliquus strai...…”
Section: Introductionmentioning
confidence: 99%
“…A number of publications during 2012–2013 reported extracts or structurally uncharacterized marine compounds, with novel and interesting preclinical and/or clinical pharmacology: in vitro antimalarial activity in crude extracts from Fiji marine organisms using a semi-automated RNA fluorescence-based high-content live cell-imaging assay [10]; the first report of in vitro liver stage antiplasmodial activity and dual stage inhibitory potential of British seaweeds [11]; anti-hepatitis C virus activity affecting the viral helicase NS3 and replication, in crude extracts from the marine feather star Alloeocomatella polycladia [12]; anti-herpes simplex virus HSV-1 and HSV-2 activity in a purified sulfoglycolipid fraction from the Brazilian marine alga Osmundaria obtusiloba [13]; in vivo anti-inflammatory activity of a heterofucan from the Brazilian seaweed Dictyota menstrualis that inhibited leukocyte migration to sites of tissue injury by binding to the cell membrane [14]; in vivo antinociceptive and anti-inflammatory activity in a crude methanolic extract of the red alga Bryothamnion triquetrum [15]; in vivo anti-inflammatory activity in a sulfate polysaccharide fraction from the red alga Gracilaria caudata resulting in significant inhibition of neutrophil migration and cytokine release [16]; in vitro anti-inflammatory effect of a hexane-soluble fraction of the brown alga Laminaria japonica that inhibited nitric oxide, prostaglandin E 2 , interleukin (IL)-1β and IL-6 release from lipopolysaccharide-stimulated macrophages via inactivation of nuclear factor-κB transcription factor [17]; in vivo anti-inflammatory of a polysaccharide-rich fraction from the marine red alga Lithothamnion muelleri that reduced organ injury and lethality, as well as pro-inflammatory cytokines and chemokines, associated with graft-versus-host disease in mice [18]; in vivo clinical effectiveness in an osteoarthritis trial by PCSO-524 TM , a nonpolar lipid extract from the New Zealand marine green lipped mussel Perna canaliculus , which may offer “potential alternative complementary therapy with no side effects for osteoarthritis patients” [19]; enhanced antioxidant activity of chitosan nanoparticles as compared to chitosan on hydrogen peroxide-induced stress injury in mouse macrophages in vitro [20]; induction of concentration-dependent vasoconstrictive activity on isolated rat aorta by a tentacle extract from the jellyfish Cyanea capillata [21]; significant antioxidant effect of a sulfated-polysaccharide fraction of the marine red alga Gracilaria birdiae which prevented naproxen-induced gastrointestinal damage in rats by reversing glutathione depletion [22]; in vitro antioxidant properties of a polysaccharide from the brown seaweed Sargassum graminifolium (Turn.) that was also observed to inhibit calcium oxalate crystallization, a constituent of urinary kidney stones [23]; antioxidant activity in organic extracts from 30 species of Hawaiian marine algae, with the carotenoid fucoxanthin identified as the major bioactive antioxidant compound in the brown alga T. ornata [24]; screening of antioxidant activity in 18 cyanobacteria and 23 microalgae cell extracts identified Scenedesmus obliquus strai...…”
Section: Introductionmentioning
confidence: 99%
“…The venom of the giant jellyfish Nemopilema nomurai , administrated intravenously in rats, induces dose-dependent hypotension and bradycardia (0.1-2.4 mg protein/kg); this venom also produces contraction of isolated rat aortic rings [35]. Tentacle extract from the jellyfish Cyanea capillata induces contraction in both endothelium-intact and endothelium-denuded isolated aortic rings [36]. In other studies, it was found that aqueous extracts from the calcareous hydrozoans M. alcicornis and M. complanata induce vasoconstriction of isolated rat aortic rings [37, 38].…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that the presence of PLA 2 enzymes in cnidarian venoms plays an important role in defense against predators, and in the immobilization and digestion of prey [20, 44]. Moreover, some studies have related PLA 2 activity to hemolysis [36, 46]. …”
Section: Discussionmentioning
confidence: 99%
“…The isolated tentacles were placed in plastic bags with dry ice and immediately shipped to Shanghai, where the samples were stored in a -80 °C freezer until use. The TE preparation procedure has been described in previous reports ( Wang et al 2013a;Wang et al 2013b;Wang et al 2013c;Wang et al 2013d;Zhang et al 2014). Briefly, tentacles at -80 °C were thawed and immersed in seawater (28 g/L NaCl, 5 g/L MgCl 2 •6H 2 O, 0.8 g/L KCl, 1.033 g/L CaCl 2 ) to allow tissue autolysis and stirred gently for 4 days.…”
Section: Preparation Of Tentacle Extract From the Jellyfish C Capillatamentioning
confidence: 99%